Bacillus sp. isolated from banana waste and analysis of metabolic pathways in acidogenic systems in hydrogen production. (1st October 2019) - Mazareli, Raissa Cristina da Silva; Sakamoto, Isabel Kimiko; Silva, Edson Luiz; Varesche, Maria Bernadete Amâncio
Abstract: The autochthonous bacterial strain was isolated from banana waste (BW) for hydrogen production and organic acids from different pure substrates and BW. The potential production of H2 and metabolic pathways were analyzed at pH 7.0 at 37 °C. Facultative anaerobic bacterium similar to Bacillus sp. was identified, with generation time (Tg) and growth rate (μ) of 0.43 h and 1.60 h −1, respectively, from glucose. The hydrogen production ( P ) using pure substrates was observed between 10.81 mmol.L −1 and 17.75 mmol.L −1 from xylose and maltose, respectively. The biggest and smallest hydrogen P of 18.77 mmol.L −1 and 1.72 mmol.L −1, were obtained with 3.5 and 0.5 g.L −1 of cellobiose, respectively. The highest hydrogen yield (126.93 mL.g −1 carbohydrates added ) was obtained with 2 g.L −1 cellobiose. In the assay using banana waste (5 g.L −1 ) the maximum P and yield (YH2 ) of 31.7 mmol.L −1 and 94.66 mL H2 g −1 carbohydrates added, was obtained respectively. The main metabolic pathway of hydrogen production by Bacillus sp. RM1 from banana waste was acetic-butyric acid of 487.69 g.L −1 and 535.88 g.L −1, respectively. The accessibility of various carbon sources by Bacillus sp. RM1 in fermentation can benefit the hydrogen production from complex organic substrates in the bioaugmentation process. Highlights: Bacillus sp. RM1 was isolated from banana waste (BW). H2 yield of 126.93 mL H2 g-1carbohydrates added was achieved for 2.5 g cellobiose.L-1. The H2 yield from BW was 1.8 times higher than using pure sugars. End products from BW conversion were acetic acid, butyric acid, caproic acid and ethanol. Maximum H2 production of 31.7 mmol.L-1 was obtained from fresh BW in 20 h.